The Role of Digital Media in Accounting Transparency and Corporate Image: SDGs Communication Approach - Irfan Sophan; Ade Sudarma; Tina Kartini; Andri Indrawan; Kanyapat Pattanapokinsakul (Communicatus: Jurnal Ilmu komunikasi, 2025)
Digital media is crucial in supporting accounting transparency and shaping a company's strategic image in the digital era. This article examines how a value-based communication approach can integrate the principles of Sustainable Development Goals (SDGs) into corporate communication practices, particularly regarding accountability and reputation. By optimizing digital media, companies enhance the transparency of financial information and build public trust through narratives aligned with sustainability values. This study employs a descriptive qualitative approach with case study analysis on companies adopting value-based communication strategies. The findings show that the synergy between digital media and SDG values can improve public perception of corporate social responsibility and ethics. This also strengthens the company's strategic position in the eyes of stakeholders, creating a positive image and fostering long-term relationships with various parties involved. Through this integration, companies can achieve financial transparency and a strong reputation.